(untitled) (Journal of the College of Basic Education, 2022)
It is a matter of pride and pride that I present the fruit of my humble effort represented in this research, which came under the title (The breadth of semantic issues in the approach of Dr. Mustafa Jawad) as a way towards the movement of our language and its help in facing the developments of the times and the progress of civilization, as I moved in it between sources and references in order to come out in its current form and what increases it A new addition, and all my concern was focused on producing it in a proper manner that would increase the status of Dr. Mustafa Jawad and open new horizons in the expansion and development of the language and be the first building block for other research and studies.